Ultrasound vs. standard radiography to determine peripherally-inserted central catheter tip location - Thimoty, James; Ifran, Evita Karianni B.; Rohsiswatmo, Rinawati (Indonesian Pediatric Society, 2024)
Background The use of a peripherally-inserted central catheter (PICC) has increased in preterm neonates to facilitate the administration of total parenteral nutrition. Standard radiography (thoracoabdominal X-ray) is the gold standard for determining the position of the PICC tip. However, radiography is not always accurate, influenced by the position of the extremities and anatomic variations, time-consuming procedural process, involves radiation, and is costly. Ultrasonography (USG) may serve as an easier, safer, less costly, and more real-time alternative in the neonatal intensive care unit (NICU) patients. Objective To assess the accuracy of USG use in determining PICC tip position compared to that of standard radiography. Methods This diagnostic study was conducted in the NICU at Dr. Cipto Mangunkusumo Hospital, Jakarta. The PICCs were placed using standard NICU procedure, then the tip position was evaluated using the USG immediately before standard radiography was performed. A 2x2 table was constructed to compare the diagnostic accuracy of the two modalities. Results A total of 29 neonates were included in our study. Subjects’ mean gestational age and weight were 31.7 weeks and 1,618.9 g respectively. Concordance of PICC tip positioning between standard radiography and USG occurred in 27 neonates (93.1%). USG had 88.89% sensitivity, 95% specificity, and 93.1% diagnostic accuracy. Conclusion USG has excellent diagnostic accuracy for confirmation of the PICC tip position.